Evaluasi Sifat Fisika Tanah Pada Lahan Pertanian Berbasis Agroekologi - Laoli, Desta Ewini; Mendrofa, Serlin Jessica (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Agroecological approach in agricultural land management is increasingly important to achieve sustainability in the agricultural sector. This study aims to evaluate the physical properties of soil on agroecological-based agricultural land compared to conventional agricultural land. The parameters measured include soil texture, structure, porosity, water retention capacity and infiltration rate. The research results show that agroecological land has better physical soil quality, characterized by a more crumbly soil structure, higher porosity and water retention capacity, and a better infiltration rate than conventional land. This increase is due to agroecological management practices that emphasize the use of organic materials and soil conservation. The conclusions of this research indicate that an agroecological approach can improve soil health and has the potential to support sustainable agricultural productivity. The results of this research support further implementation of agroecological practices to improve soil quality on agricultural land.